Simply Construction Method for Exponential Source’s Scalar Quantizers - Nikolic, J.; Antic, D.; Peric, Z. (Elektronika ir Elektrotechnika, 2005)
In this paper we consider methods for determining necessary parameters for constructions of the scalar quantizers for exponential source. There are two approaches to the problem of finding the sets of optimum parameters. One is an exact solution based on an iterative procedure, and another, that we suggested, is an approximation method for solving transcendental equations. This method can be used for simply and fast finding for solutions which are very close to the exact solutions. Ill. 2, bibl. 5 (in English; summaries in Lithuanian, English and Russian).